Teaching with digital badges best practices for libraries - Jacobson, Trudi E. 1957-; O'Brien, Kelsey 1986- (Innovations in information literacy, 2018)
"Teaching with Digital Badges: Best Practices for Libraries provides examples of how badges are enhancing and invigorating information literacy instruction. The editors share their experience implementing a metaliteracy badging system that has engaged more than 2,000 students across disciplines, secured faculty buy-in, and facilitated partnerships"--Provided by publisher.